Substitusi Tepung Tempe Sebagai Sumber Zat Besi Terhadap Karakteristik Organoleptik Sosis Ikan Teri - Siti Sania Bilqis; Ibnu Malkan Bakhrul Ilmi; Muhammad Nur Hasan Syah; Nanang Nasrullah (Program Studi Teknologi Pangan, 2022)
Anemia is a global health problem that affects a third of the world's population, one of which is the lack of iron-containing food sources. The aim of this study was to analyze the nutritional content, iron content, and organoleptic properties of the selected formulation of anchovy sausage substituted with tempeh flour as an iron-rich snack. This study used a one-factor Completely Randomized Design (CRD) method with three different treatments and two repetitions. The proportions of tempeh flour with anchovy are F1 (35:45), F2 (40:40), and F3 (45:35). The results of the ANOVA test showed that there was no significant effect (P>0.05) on water content, ash content, protein content, fat content, carbohydrate content, and iron content. The results of the Kruskal-Wallis test showed that there was no significant effect (p>0.05) on the panelists' preference for color, aroma, taste, and texture characteristics. The sausage formula was selected through the exponential comparison method (MPE), namely the F3 formula. The serving dose of the selected formula sausage has an energy content of 228 kcal; protein 16.4 g; fat 11.3 g; carbohydrates 15 g; 2.4 mg of iron in one serving, which is 100 grams.